RESPON TIGA VARIETAS UBI JALAR (Ipomoea batatas L.) TERHADAP PEMUPUKAN KALIUM - Petrus, Santo; Lestari, Sri Umi; Indawan, Edyson (Universitas Tribhuwana Tunggadewi, 2018)
The objective of this research is to evaluate influence dosage of potassium fertilizer on increasing the size and yield of sweet potato variety. Treatment arranged by Strip plot design consist of two factors. First factor consist of three variety of sweet potato (Sari, Jago, and Boko). and the second factor is dosage of potassium fertilizer (K0: 0 kg KCl. ha-1, K1: 133 kg KCl. ha-1, K2:333 kg KCl. ha-1, and K3: 533 kg KCl. ha-1). Size of the plot are 1,5 m x 5 m consist of 5 rows, planted with a spacing of 25 cm in rows. The plants are harvested at 4 months after planting, based on several parameters,ie the number of storage root, fresh storage rroot weight, fresh weight of stover, percentages of storage root dry matter and stover dry matter, dry weight of storage root and stover, dry weight of biomass, and harvest index, number of large storage root, number of medium storage root, number of small storage root, large storage root weight, medium storage root weight, small storage root weight, ratio of large, medium, and small storage root weight to storage root total, and size of storage root (g/storage root). The result showed that distribute potassium fertilizer does not influence the parameter of root weight, storage root dry weight precentage, stover dry weight precentage, dry weight of storage root, harvest index, number of large storage root, large storage root weight, medium storage root weight, and ratio of small storage root weight. There was different at number of storage root, stover weight, dry weight of stover and the biomass. There is interaction between varieties with dosage of potassium fertilizer on storage root size parameters, namely Sari with dosage 333 kg KCl ha-1 gives the highest storage root size of 138.86 g/storage root. In Jago clone the highest storage root size of 198.46 g/storage root with potassium dosage 0 kg KCl. ha-1. While at variety of Boko, the highest storage root size is found in potassium dosage 133 kg KCl. ha-1 produce storage root size 166.92 g/storage root. Tujuan dari penelitian ini adalah untuk mengevaluasi pemberian dosis pupuk kalium terhadap peningkatan ukuran dan hasil varietas ubi jalar. Rancangan percobaan strip plot yang terdiri dari dua faktor. Faktor pertama tanaman ubi jalar yang terdiri dari tiga varietas (Sari, Jago dan Boko). Faktor kedua adalah dosis pupuk kalium terdiri dari 4 level dosis (K0: 0 kg KCl/ha, K1: 133 kg KCl/ha, K2:333 kg KCl/ha, dan K3: 533 kg KCl/ha). Ukuran petak percobaan 1,5 m x 5 m terdiri dari 5 gulud, masing-masing ditanami stek dengan jarak tanam dalam baris 25 cm. Tanaman di panen saat berumur 120 HST berdasarkan parameter pengamatan jumlah umbi, bobot segar umbi, bobot segar brangkasan, bobot kering umbi, bobot kering brangkasan, bobot kering biomass, persentase bobot kering umbi, persentase bobot kering brangkasan, indeks panen, jumlah umbi besar, jumlah umbi sedang, jumlah umbi kecil, bobot umbi besar, bobot umbi sedang, bobot umbi kecil, ratio bobot umbi sedang/total umbi, ratio bobot umbi kecil/total umbi, dan ukuran umbi (g/umbi). Hasil penelitian menunjukan bahwa pemberian pupuk kalium tidak mempengaruhi parameter bobot umbi, persentasi bobot kering umbi, persentasi bobot kering brangkasan, berat kering umbi, indeks panen, jumlah umbi besar, bobot umbi besar, bobot umbi sedang, dan ratio bobot umbi kecil. Berbeda nyata pada jumlah umbi, bobot brangkasan, berat kering brangkasan dan biomass. Terdapat interaksi antara varietas dengan pemberian kalium pada parameter ukuran umbi yaitu klon sari dengan dosis kalium 333 kg KCl/ha memberikan ukuran umbi tertinggi sebesar 138.86 g/umbi. Pada klon jago ukuran umbi tertinggi sebesar 198.46 g/umbi dicapai tanpa pemberian dosis kalium 0 kg KCl/ha. Pada klon boko ukuran umbi tertinggi terdapat pada dosis kalium 133 kg KCl/ha menghasilkan ukuran umbi sebesar 166.92 g/umbi.